1963
DOI: 10.1177/00220345630420031301
|View full text |Cite
|
Sign up to set email alerts
|

Interglobular Dentin in the Deciduous Tooth

Abstract: Interglobular dentin formation, as described in textbooks of dental histology,' 2 is the result of normal matrix formation but failure of complete fusion of the calcospherites during the calcification period that follows.Schour and Poncher,3 Kronfeld and Schour,4 and Blackerby5 have observed that in deciduous teeth the prenatal dentin appeared homogeneous without interglobular spaces, whereas postnatal deciduous dentin contained varying intensities of interglobular space formation. These observations and the u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
8
0

Year Published

1969
1969
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 1 publication
0
8
0
Order By: Relevance
“…If there are adequate nutritional conditions during the processes of formation and calcification, the matrix will appear homogenous and fusion of calcospherites, spheres containing calcium salts, will be complete (D'Ortenzio et al, ; Hillson, ). However, when vitamin D levels are inadequate, some of the calcospherites fail to fuse, which is visible as poorly mineralized patches of dentine with a bubble‐like appearance, referred to as IGD (D'Ortenzio et al, ; Isokawa, Kosakai, & Kajiyama, ; Vital et al, ). The presence of IGD is clinically associated with conditions disrupting mineralization by affecting vitamin D, calcium and/or phosphate levels (Chaussain‐Miller et al, ; McDonnell, Derkson, Zhang, & Hlady, ; Souza, Soares, Alves dos Santos, & Vaisbisch, ; Vital et al, ).…”
Section: Methodsmentioning
confidence: 99%
“…If there are adequate nutritional conditions during the processes of formation and calcification, the matrix will appear homogenous and fusion of calcospherites, spheres containing calcium salts, will be complete (D'Ortenzio et al, ; Hillson, ). However, when vitamin D levels are inadequate, some of the calcospherites fail to fuse, which is visible as poorly mineralized patches of dentine with a bubble‐like appearance, referred to as IGD (D'Ortenzio et al, ; Isokawa, Kosakai, & Kajiyama, ; Vital et al, ). The presence of IGD is clinically associated with conditions disrupting mineralization by affecting vitamin D, calcium and/or phosphate levels (Chaussain‐Miller et al, ; McDonnell, Derkson, Zhang, & Hlady, ; Souza, Soares, Alves dos Santos, & Vaisbisch, ; Vital et al, ).…”
Section: Methodsmentioning
confidence: 99%
“…Investigators including KATAYAMA [7], NISHIYAMA [8], EVRA [9], NAKAJIMA [10] and ISOKAWA et al [11] all confirmed the existence of interglobular space in human teeth with nearly 100 % occurrence. With other mammalian teeth, however, the existence of this interglobular space has not been confirmed.…”
Section: Observationsmentioning
confidence: 99%
“…
KOLLMANN[5] to be that portion of hypocalcified area occured by an imperfect union of calcospherites appearing in the calcification of dentin through its formative process.In the published native literature, ISOKAWA et al[6] established the interglobular space as an imperfectly calcified portion as a result of their historadiographic analysis.In an effort to study universal morphology of the interglobular space, KATAYAMA [7], NISHIYAMA [8], ERVA [9] and NAKAJIMA[10] used the permanent teeth, whereas ISOKAWA et al [11] made use of the deciduous teeth, the latter carrying out observations by means of semi-serial ground sections. Consensus of their opinions indicates that the interglobular space can be regarded as a universal structure except for the deciduous incisors and canines in man.

On the other hand, FUJITA [12] in his textbook on Dental Histology describes that the interglobular space is altogether lacking in teeth other than those of man and, if there should be found at all, it is a very rare phenomenon.

…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Morphological studies on the interglobular dentin that exists in human teeth are under way using microradiography [1,2] or scanning electron microscopy [3]. Dept.…”
Section: Introductionmentioning
confidence: 99%